Analisis Representasi Budaya Kajian Hermeneutika pada Film Budi Pekerti Karya Wregas Bhanuteja - A'yun, Rofatul; Sugianti, Sugianti; Rosidah, Ilmiyatur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to determine the cultural representation of hermeneutic studies in the film "Budi Pekerti" by Wregas Bhanuteja. This study began with the author who was offended after watching the film "Budi Pekerti" where the film touched on the culture of social media ethics which in the current era is almost not applied by social media users. This is the reason why the author finally chose this film as the material for analysis. This study uses a descriptive method with a qualitative approach with a hermeneutic study from Richard Palmer which uses three aspects, namely To Say, To Explain and To Translate. The subject of this study is the film "Budi Pekerti" by Wregas Bhanuteja. While the object of this study is the representation of culture in the film. The instruments in this study are secondary instruments and primary instruments. The secondary instrument is a separate study while the primary instrument uses a data collection table. The data in this study are in the form of dialogue, narration and also speech in the film. Data sources are obtained from films watched on the Netflix channel. The data collection technique in this study uses the Listen and Note Technique. While the analysis technique uses the Data Collection Technique, Data Reduction, Data Presentation and Conclusion Drawing. The most dominant result of the cultural representation research is the aspect to explain with indicators of strength and power, especially in social media. In this film, many use explanations to communicate and assert their power and authority in various situations. It can be seen that the culture of norms and politeness, especially in the Javanese context, appears in a distinctive way in the Budi Pekerti film. Keywords: cultural representation, hermeneutics, Budi Pekerti film.